Gold-catalyzed formal 1,6-acyloxy migration leading to 3,4-disubstituted pyrrolidin-2-ones - Hashmi, A. Stephen K.; Yang, Weibo; Yu, Yang; Hansmann, Max M.; Rudolph, Matthias; Rominger, Frank (Angewandte Chemie. International edition, 2013)
Mobile: The title reaction affords diastereomerically pure 3,4-disubstituted pyrrolidin-2-ones, which are important structural motifs in natural products, in good to high yields. Mechanistic investigations suggest the transformation proceeds through a tandem 1,3-acyloxy migration and a subsequent 1,5-acyloxy migration. DCE=1,2-dichloroethane, IPr=1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene.